Job Involvement Reality in Physical Education Supervisors in General Educational Bureaus Directorate in Iraq - Ahmed Khyoon Hashem; Thamer Hemad Reja (College of Physical Education and Sport Sciences, 2020)
The research aimed at identifying job involvement in physical education supervisors in the Iraqi general educational directorate. The researchers used the descriptive method on (492) physical education supervisors from (20) directorates. A scale was designed of four fields distributed on (3) items arranged in the form of a questionnaire. The data was collected and treated using SPSS. The results showed that designing a measurement is of great importance to detect the level of job involvement in physical education supervisors and their daily administration of work to improve and evaluate physical education class as well as programs designed for students. The researchers finally recommended adapting measurement as a means for discovering the degree of job involvement for producing new, distinguished products. In addition to that, they recommended listening to supervisors' suggestions and giving them the freedom of speech a matter that motivates them for better job involvement and developing for the better.